Musicality and Age Interaction in Tone Development - Rhee, Nari; Chen, Aoju; Kuang, Jianjing (Frontiers in Neuroscience, 2022)
Vocal pitch, which involves not only F0 but also multiple covarying acoustic cues in the spectrum, is central to linguistic perception and production at various levels of prosodic structure. Recent studies on first-language development have shown that differences in learners' musicality affect the F0 cue development in perception of sentence-level intonation or in prosodic realisation of focus. This study aims to contribute towards a fuller understanding of the effect of musicality on linguistic pitch development via a close investigation of the relationship between musicality, age, and lexical tone production covering both F0 and spectral cues in children. Forty-three native Mandarin-speaking children between the ages of 4 and 6 years are recruited to participate in both a semi-spontaneous tone production task and a musicality test. For each age (4, 5, and 6 years) and musicality (below or above the median score of each age group) group, the contrastivity of the four tones is evaluated by performing automatic tone classification using three sets of acoustic cues (F0, spectral cues, and both). Results suggest that at the age of 4 and 5 years, higher musicality is associated with higher contrastivity of the tones produced, but not for the 6-year-olds. The findings of this study reveal that musicality promotes earlier development of tone production only in earlier stages of prosodic development; by the age of 6 years, the musicality advantage in tone production subsides.